2017
DOI: 10.1016/j.memsci.2016.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between permeation and deformation for porous membranes

Abstract: Most polymeric membranes are engineered to have high porosity in order to reduce transport resistance of the permeate(s). However, since most polymers are relatively compliant and exhibit time-dependent behavior, such membranes are prone to deformation under mechanical loading that can occur during different stages of manufacturing as well as during separation. Therefore, it is of critical importance to understand the influence of mechanical deformation on the permeability of the membranes. However, an appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…This supports the measurements made by the permeameter method and confirms that permeability is strongly dependent on the porosity and microstructure of the porous medium [5,8,36].…”
Section: Resultssupporting
confidence: 87%
“…This supports the measurements made by the permeameter method and confirms that permeability is strongly dependent on the porosity and microstructure of the porous medium [5,8,36].…”
Section: Resultssupporting
confidence: 87%
“…Combining the AFM and SEM measurements, it is evident that most of the plastic deformation occurred in the porous support, specifically in regions with higher porosity and larger pore size. This type of non-uniform deformation is expected for asymmetric porous membranes under uniaxial compression [25]. Regions with higher porosity and larger pore size will have both lower elasticity and yield strength, and will experience more densification.…”
Section: Resultsmentioning
confidence: 99%
“…Such compressive deformation is greatly accelerated during NIL processing where higher pressures and temperatures are used. Mechanically, membranes subjected to higher initial compressive strain will have higher mechanical strength due to reduced porosity of the porous support [25], and thus experience less de-formation during DI water permeation. For example, it is a common practice in research studies to subject membranes to a pressure higher than the normal operating pressure for a specific duration in order to obtain a more stable flux for subsequent continuous operation [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Directly scaling our areal production rate to ∼40 inch wide rollers (with complementary‐sized flexible patterning molds) provides ∼0.16 m 2 /min at room temperature. In prior studies of NIL membrane fabrication at elevated temperatures it was clearly shown that increasing the temperature allows similar fidelity of pattern transfer with lower contact time and forces. This would translate to higher rolling velocities in the R2RNIL process and will be studied further in our ongoing research.…”
Section: Discussionmentioning
confidence: 99%